The curse of Ham : race and slavery in early Judaism, Christianity, and Islam - Goldenberg, David M., 1947- (Jews, Christians, and Muslims from the ancient to the modern world., 2003)
How old is prejudice against black people? Were the racist attitudes that fueled the Atlantic slave trade firmly in place 700 years before the European discovery of sub-Saharan Africa? In this groundbreaking book, David Goldenberg seeks to discover how dark-skinned peoples, especially black Africans, were portrayed in the Bible and by those who interpreted the Bible--Jews, Christians, and Muslims. Unprecedented in rigor and breadth, his investigation covers a 1,500-year period, from ancient Israel (around 800 B.C.E.) to the eighth century C.E., after the birth of Islam.